(untitled) - Howard, Ronald A. (Boston, Mass., 2008)
Minor ethical lapses can seem harmless, but they instill in us a hard-to-break habit of distorted thinking. Rationalizations drown out our inner voice, and we make up the rules as we go. We lose control of our decisions, fall victim to the temptations and pressures of our situations, taint our characters, and sour business and personal relationships.
Keywords: Vấn đề đạo đức,Ethical problems